2023
DOI: 10.5455/javar.2023.j650
|View full text |Cite
|
Sign up to set email alerts
|

Survivability of Lactobacillus plantarum in nutmeg (Myristica fragrans Houtt) flesh extract and its effect on the performance of broiler chicken

Abstract: Objective: This study aimed to see if increasing the concentration of nutmeg flesh extract in vitro could increase the growth of Lactobacillus plantarum bacteria and if it had any effect on broiler chicken performance. Materials and Methods: Different concentrations of nutmeg flesh extract (5, 10, 15, and 20/100 ml distilled water) were combined with 10 ml L. plantarum (bacterial concentration 1 × 109 cfu/ ml) to produce synbiotics. A total of 250 unsexed Lohmann broiler chickens were reared together from 0 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The relative thymus weight was below the normal size, while that of the spleen and bursa Fabricius was within the normal range. The normal size of the bursa Fabricius and thymus of broilers aged 42 days was 0.09% and 0.48% of live weight, respectively [ 24 ], and the spleen ranged from 0.07% to 0.26% [ 17 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative thymus weight was below the normal size, while that of the spleen and bursa Fabricius was within the normal range. The normal size of the bursa Fabricius and thymus of broilers aged 42 days was 0.09% and 0.48% of live weight, respectively [ 24 ], and the spleen ranged from 0.07% to 0.26% [ 17 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Sapsuha et al [ 17 ], Wulandari et al [ 18 ], and Cholis et al [ 4 ], Lactobacillus is a probiotic that is frequently utilized in broilers . Furthermore, Shoeib and Madian [ 19 ] and Sugiharto et al [ 20 ] reported that an example of this probiotic is Lactobacillus acidophilus , which naturally resides in the animals’ digestive tract.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research results show that nutmeg flesh extract can maintain the survivability of L. plantarum so that it can be used as a synbiotic in broiler chickens (Sapsuha et al 2023a). It was further found that giving it to broiler chickens can improve performance and intestinal morphology and improve intestinal microbes (Sapsuha et al 2023b), but its effect on broiler chickens reared at high densities has never been studied.…”
Section: Introductionmentioning
confidence: 99%